LINGUISTIC CHARACTERISTICS OF THE CONSTRUCT "EVALUATIVE JUDGEMENT OF A JOURNALIST" IN THE UKRAINIAN LANGUAGE - Zoriana Haladzhun (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2019)
The article outlines lingual features of the "evaluative judgement" construct, being new for the Ukrainian journalistic practices. By means of analysing the structural elements of this construct, the author defines its linguistic features as well as comes up with lexico-grammatical and stylistic means representing the "evaluative judgement" construct in journalistic materials. Considering the data from practical journalistic activities, the author presumes that evaluative judgements of a journalist are based on factual information and manifest themselves via vast linguistic means corpus, being much broader than the lawmaker has defined it. In the context of the problem, the paper suggests to view "the evaluative judgement of a journalist" as his/her subjective point of view, opinion on a certain subject, personal assessment of facts or events on the grounds of knowledge, experience, journalistic standards, and information obtained from open sources, based on factual information that can be introduced into media content with the help of linguostylistic means. As exemplified by media content, the author comes up with the conclusion that apart from using such linguistic means as hyperbole, allegory, satire, which are defined by the law, as well as patterns that express evaluation or uncertainty, emphasising information probability (for example, it seems to me, in my opinion, I think, etc.), the construct under analysis also manifests itself through the use of particular tense and voice forms, impersonal constructions, complex attributive groups, complex sentences, etc. The author suggests applying the obtained results to form professional competence of both students of journalism departments and creative mass media specialists in order to ensure secure implementation of their duty to inform.